ENHANCING STUDENTS’ ENGLISH ABILITY BY USING REALIA - Rengganis Siwi Amumpuni; Brigitta Septarini Rahmasari (Jurnal Pendidikan Edutama, 2019)
Abstract: The aim of the research is to know the strenghts and weaknesses of using realia. The reseacher used classroom action research. The research was conducted in two cycles. Each cycle consisted of four steps. They are planning, acting, observation, and reflecting. In collecting the data, the researcher used test, interview, and observation. In analyzing the data, the researcher used statistic descriptive. The research implementations showed that there was an improvement in students’ speaking ability after Realia implemented in the teaching and learning process, and the students showed better achievement in speaking ability. The strengths were the students become active in classroom, enthusiastic, excited and motivated in the class. The students give more attention to the lesson and they were attracted to do the exercise during teaching learning process. The students more focused to the lesson during the activity in teaching learning process. The activities of Realia is attracted the students’ motivation and interested to the students. The researcher found that that Realia make the class becomes conducive. Meanwhile the weaknesses of using realia are the student had a difficulties to speak something caused of the limited vocabularies and confused how to pronounce the word in English and it spends much time to prepare the media. Keywords :Realia, English ability, Enthusiastic Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui kekuatan dan kelemahan menggunakan realia. Peneliti menggunakan penelitian tindakan kelas. Penelitian ini dilakukan dalam dua siklus. Setiap siklus terdiri dari empat langkah yaitu perencanaan, tindakan, observasi, dan refleksi. Dalam mengumpulkan data, peneliti menggunakan tes, wawancara, dan observasi. Dalam menganalisis data, peneliti menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa ada peningkatan kemampuan berbicara siswa setelah Realia diimplementasikan dalam proses belajar mengajar, dan siswa menunjukkan prestasi yang lebih baik dalam kemampuan berbicara. Kekuatan menggunakan realia adalah siswa menjadi aktif di kelas, antusias, bersemangat dan termotivasi di kelas. Para siswa lebih memperhatikan pelajaran dan mereka tertarik untuk melakukan latihan selama proses belajar mengajar. Para siswa lebih fokus pada pelajaran selama kegiatan belajar mengajar. Kegiatan Realia menarik motivasi siswa dan tertarik kepada siswa. Peneliti menemukan bahwa Realia membuat kelas menjadi kondusif. Sementara itu, kelemahan menggunakan realia adalah siswa memiliki kosakata yang terbatas dan kesulitan dalam pengucapan bahasa Inggris dan menghabiskan banyak waktu untuk mempersiapkan media.Kata Kunci: Realia, Kemampuan Bahasa Inggris, Antusias